Stable Income, Stable Family - Jason M. Lindo; Krishna Regmi; Isaac D. Swensen (Institute of Labor Economics (IZA), 2022)
We document the effect of unemployment insurance generosity on divorce and fertility using an identification strategy that leverages state-level changes in maximum benefits over time and comparisons across workers who have been laid off and those that have not been laid off. The results indicate that higher maximum benefit levels mitigate the effects of layoffs. In particular, they mitigate increases in divorce associated with men's layoffs; increases in separations associated with women's layoffs; reductions in fertility associated with men's layoffs; and increases in fertility associated with women's layoffs.
Keywords: J12; J13; J16; J65; H53; I38; 330; unemployment insurance; job loss; marriage; divorce; fertility; gender; family